Effect of cation vacancies on the optical and dielectric properties of KSr2Nb5O15: A first‐principles study. Issue 3 (28th November 2019) - Chen, Qian; Gao, Feng; Xu, Jie; Wu, Changying; Cao, Shuyao; Guo, Yiting; Pawlikowska, Emilia; Szafran, Mikołaj; Cheng, Guanghua
Abstract: Using first‐principles calculations, the effect of cation vacancies on the electronic structures and optical characters of KSr2 Nb5 O15 (KSN) lead‐free ferroelectrics are investigated. The calculated dielectric properties are demonstrated by the experimental results. The cation vacancies involve K + vacancies (KSN‐K), Sr 2+ vacancies (KSN‐Sr), and coexisting K + and Sr 2+ vacancies (KSN‐K&Sr). When these cation vacancies exist in KSN, the unit cell volumes decrease, leading to phase transition from tetragonal to orthorhombic, and the cation vacancies show strong effects on the band gap of KSN, declining by 1.46%‐9.46%. The optical properties including the static dielectric constants, refraction, and extinction coefficient of KSN‐K, KSN‐Sr, and KSN‐K&Sr increase more than those of KSN without vacancies, but the reflectivity and loss function decrease. All structures with cation vacancies are mainly refractive in the 0‐4 eV photon energy range and are reflective at 5‐8 eV. The refractivity increases and reflectivity decreases after vacancies occur. KSN‐Sr has the largest static dielectric constant while KSN‐K&Sr has the smallest values. The dielectric constant can be adjusted in the range of 25% by controlling the cation vacancies. The calculated dielectric properties are in good agreement with the experimental results. The results pave the way to regulate the optical and dielectric properties of lead‐free ferroelectrics by controlling different cation vacancies. Abstract : The optical and dielectric properties of KSr2 Nb5 O15 (KSN) lead‐free ferroelectrics with cation vacancies have been studied in this work. The abstract graphic is made up of two parts, the left part is the first principle calculation results including lattice structures and electronic structures of KSN‐K (KSN with K + vacancy), KSN‐Sr (KSN with Sr 2+ vacancy) and KSN‐K&Sr (KSN with coexisting K + and Sr 2+ vacancies), as well as the absorption dependent on the photon energy and wavelength. The right part is the experimental results of dielectric properties and transmittance of KSN (KSN‐K&Sr), KSN‐4K (KSN‐Sr) and KSN‐4Sr (KSN‐K). From the absorption and reflectivity by first principles, the transmittance can be obtained, which is in good agreement with our experimental results of transmittance T( ω )KSN‐4Sr < T( ω )KSN < T( ω )KSN‐4K.